Understanding Psychological Connections to Dietary Behavior: A Study of Future Medical Professionals' Knowledge and Insights - Ajaz, Madiha; Ajaz, Misbah; Asif, Hafsa; Saeed, Anam; Sahar, Tuba; Alam, Farhad; Sajjad, Qamar; Sarwar, Farzana (Indus Journal of Bioscience Research, 2025)
Background: Eating disorders are not a lifestyle of choice rather illnesses that are of serious concern. Eating disorders pose a huge global burden. Body dissatisfaction, overweight in childhood and various other factors has increased the risk of having eating disorders. Different studies conducted in Pakistan conclude that a significant fraction of medical university students is at risk of having Eating Disorders. Methods: A cross-sectional study was conducted among 834 participants from Dow medical college and Dow international medical of Karachi. Participants of the study were recruited through convenient sampling technique, by signing an informed consent. Data was collected using self-administered questionnaire, which included 26 items in total. Initial questions were about the demographic details of the participants and there were twenty questions to assess participants’ knowledge about eating disorders. This data was analyzed and presented using SPSS version 16 along with Office word format and excel. Results: Overall, the average number of correct responses to eating disorders terminology and characteristics related questions was 6.88 ± 1.94 (out of 10 questions). Mean score for knowledge about eating disorders assessment and terminology was 6.55 (out of 10 questions) with a standard deviation of ±1.68. Participants’ sex, age, and level of education were found to be significantly associated with their knowledge about eating disorders. Conclusion: Eating disorders are serious medical conditions, yet students lack adequate understanding regardless of gender or university. While higher study levels show a slight positive impact, attention must be given to curriculum, teaching hours, and clinical exposure for eating disorders.